Inhibition of 5-lipoxygenase attenuates inflammation and bone resorption in lipopolysaccharide-induced periodontal disease - Lopes, Debora E. M. [UNESP]; Jabr, Camila L. [UNESP]; Dejani, Naiara N. [UNESP]; Saraiva, Amanda C. [UNESP]; Aquino, Sabrina G. de [UNESP]; Medeiros, Alexandra I. [UNESP]; Rossa Junior, Carlos [UNESP] (Amer Acad Periodontology, 2018)
BackgroundArachidonate-5-lipoxygenase (5-LO) activity and increased leukotriene B4 (LTB4) production have been implicated in various inflammatory conditions. Increased production of leukotrienes has been associated with periodontal diseases; however, their relative contribution to tissue destruction is unknown. In this study, an orally active specific 5-LO inhibitor is used to assess its role in inflammation and bone resorption in a murine model of lipopolysaccharide (LPS)-induced periodontal disease. MethodsPeriodontal disease was induced in Balb/c mice by direct injections of LPS into the palatal gingival tissues adjacent to the maxillary first molars three times per week for 4weeks. Animals were treated with biochemical inhibitor (2mg/kg/daily) or the same volume of the vehicle by oral gavage. Microcomputed tomography analysis was used to assess bone resorption. Enzyme immunoassay determined LTB4, and enzyme-linked immunosorbent assays quantified tumor necrosis factor (TNF), interleukin (IL)-12, and IL-10 in gingival tissues. Histologic sections were used for the morphometric analysis (number of neutrophils and mononuclear cells). Osteoclasts were counted in tartrate-resistant acid phosphatase-stained sections. ResultsAdministration of 5-LO inhibitor effectively reduced production of LTB4 (23.7% decrease) and significantly reduced TNF and IL-12 levels in gingival tissues. Moreover, reduction of LTB4 levels in gingival tissues was associated with a significant decrease in bone resorption and a marked reduction in number of osteoclasts and inflammatory cells. Conclusion5-LO activity plays a relevant role in inflammation and bone resorption associated with the LPS model of experimental periodontal disease.
Keywords: Bone resorption; inflammation; innate immunity; leukotrienes; periodontitis